Philosophical elements of the formative educative gymnastics (Fiep Bulletin - online, 2015)
Formative-educational gymnastics banish all exercises which,  During growth, denaturalize the muscular, articular and aponevrotic functions and, consequently, the great organic functions, Together with eugenics, it seeks the means to create the most beautiful human types.